2020
DOI: 10.1111/cas.14319
|View full text |Cite
|
Sign up to set email alerts
|

Genome organization in proximity to the BAP1 locus appears to play a pivotal role in a variety of cancers

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. AbstractCancer studies primarily focus on the characterization of the key driver genes and the underlying pathways. However, the contribution of other cancer-associated genes located in the genomic neighborhood of the driver genes c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The study revealed a high occurrence of DNA methylation‐mediated changes in FHL1 gene in mouth cancer, highlighting its significant relevance in the context of epigenetics 92 . Furthermore, previous studies have indicated that the involvement of loci‐specific (specifically on the X chromosome) and global long interspersed nuclear element‐1 (LINE‐1) repetitive sequence is associated with many forms of cancer 93–95 …”
Section: Tsgs X‐linked Tsgs and Their Involvement In Cancersmentioning
confidence: 85%
See 1 more Smart Citation
“…The study revealed a high occurrence of DNA methylation‐mediated changes in FHL1 gene in mouth cancer, highlighting its significant relevance in the context of epigenetics 92 . Furthermore, previous studies have indicated that the involvement of loci‐specific (specifically on the X chromosome) and global long interspersed nuclear element‐1 (LINE‐1) repetitive sequence is associated with many forms of cancer 93–95 …”
Section: Tsgs X‐linked Tsgs and Their Involvement In Cancersmentioning
confidence: 85%
“…92 Furthermore, previous studies have indicated that the involvement of loci-specific (specifically on the X chromosome) and global long interspersed nuclear element-1 (LINE-1) repetitive sequence is associated with many forms of cancer. [93][94][95] Genes associated with cancer experience significant evolutionary selection. Researchers have proposed that Xlinked TSGs are not shielded by the Knudson's two-hit mechanism and are consequently susceptible to negative selection.…”
Section: And Evolutionary Aspectsmentioning
confidence: 99%
“…We have previously reported that PPARγ is expressed in UM, which is the most frequent primary intraocular tumor in Caucasian adults with abnormal genetic-epigenetic characteristics and metastatic potential [26,33,34]. Recently, we also reported that DNMT1, along with a few other chromatin-associated genes, is a potential miRNA target cluster embedded within one of the driver genes (BAP1) of UM [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, most of studies focused on the gene expression patterns and correlation with the clinical outcomes, mainly survival rate. None of the above-mentioned studies addressed the impact of genome organization in proximity to these genes, which is known to play a pivotal role in human diseases ( 14 ). On this note, the prevalence of repetitive sequences, especially LINEs (Long Interspersed Nuclear Elements), SINEs (Short Interspersed Nuclear Elements), Alu family in the functional parts of genomes and their association with cancers remains undisputed ( 15 17 ).…”
Section: Introductionmentioning
confidence: 99%